Re-masculinization of the teaching profession: Towards a policy of attracting, recruiting and retaining male teachers in the Trinidad and Tobago school system - Joseph, Stephen - (Advances in Social Sciences Research Journal, 2016)
In response to repeated calls for the re-masculinization of the teaching profession, some governments have implemented policy decisions aimed at attracting, recruiting, and retaining male teachers in the school system. In this qualitative study, a purposive sampling method was used to obtain information from twenty-four participants about the type of men needed in the Trinidad and Tobago school system. Findings of the study revealed that preference was given to men who are father figures and positive role models for young boys. Such individuals should also be good disciplinarians, and physically strong men who exhibit a hegemonic masculinity. While the male role model argument resonated well with many of the respondents in the study, policy brokers were advised not to use gender as the sole basis for recruiting men into the teaching profession. Rather, those persons should demonstrate sound pedagogical skills and competence in teaching all children.